Influence of selected aspects of the technical condition of means of transport operating in Greater Poland on road safety - Gorzelanczyk, Piotr (Technical Sciences, 2020)
The article evaluates the technical condition of means of transport moving around Great Poland and their impact on road safety. To this end, the number of transport vehicles registered in Poland was analyzed, and the effects of technical disability of vehicles were assessed. In addition, the following tests were carried out: examination of the technical condition of lighting, tires of means of transport. Finally, appropriate conclusions were drawn.